A CROSS-SECTIONAL STUDY ON FACTORS AFFECTING DIETARY QUALITY OF ADOLESCENTS WITH TYPE 1 DIABETES - Gülsüm Şahin Bodur; Alev Keser; Zeynep Şıklar; Merih Berberoğlu (İstanbul Tıp Fakültesi Dergisi)
Objective: The diet quality of adolescents with type 1 diabetes is shaped by some individual factors. These include age, gender, sociodemographic characteristics, lifestyle habits, and adaptation to diabetes treatment. This study aims to investigate the factors affecting the diet quality of adolescents with type 1 diabetes. Material and Methods: The sample in this study consisted of adolescents with type 1 diabetes who were followed in the Department of Pediatric Endocrinology of the Faculty of Medicine at the University of Ankara between July 2017-January 2018. The research data was collected using the face-to-face interview technique with a questionnaire. The physical activity levels of the individuals were determined using a ‘24-hour physical activity level detection form (short)’. Three-day food consumption records were taken and evaluated via BeBiS. The Healthy Eating Index-2010 was used to determine diet quality. Results: The study was conducted with a total of 110 adolescents (M:51.8%; F:48.2%) with type 1 diabetes in the 10-19 age range (mean age:14.0±2.40 years). Only 15.5% of all individuals have good diet quality. In a linear regression model formed by the variables of exercise status, physical activity type, and PAL value of individuals, a positive significant relationship was found between exercise status and diet quality (χ2 (1,n=110)=1.392, p<0.05). Conclusion: As a result, it was found that the majority of individuals needed to improve their diet quality and that exercise affected the diet quality of type 1 diabetic adolescents. In addition, exercise levels, which have an important role in both diabetes management and improvement of diet quality, should be increased.